The economics of rice farming in Dhanusha District, Nepal : production and technology adoption - Malla, Parashar Bhakta (1982)
This study is concerned with the input-output relationship in rice cultivation and examination of difference in response of modern and traditional varieties of rice with respect to the application of fertiliser. An attempt has also been made to evaluate the costs and returns of cultivating rice crop. Finally, influence of various techno-socio-economic variables that might be associated with the adoption of a modern variety rice and use of fertiliser in the rice crop has been examined. Survey data obtained by interviewing 147 farmers of selected eight Village Panchayats of Dhanusha district were used for the analytical purpose. Production function analysis was used to ascertain input-output relationship in rice cultivation. Difference in response between modern and traditional variety rice with respect to fertiliser use was also examined within production function analysis framework. Costs and returns were computed to evaluate the net returns. Maximum likelihood logit analysis was employed to determine decision regarding the adoption of modern variety rice and use of fertiliser in rice crop. Irrigation, application of compost and nitrogen appeared likely to increase the yield of rice crop. Although the response of modern variety rice to nitrogen fertiliser seemed better than that of traditional variety, the evidence was fragmentary. Net returns were found to be higher for modern variety rice than for traditional variety. Schooling, family size, paddy acreage, proportion of land area irrigated, extension visits and fertiliser use were the important variables that influenced farmers' decision to adopt a modern variety rice, while variables such as age, family size, non-farm income, paddy acreage, proportion of land irrigated, radio listening, extension visits and modern variety use were important in deciding whether to use fertiliser. Interestingly, however, schooling had negative relation in both the decisions regarding adoption of a modern variety or use of fertiliser. Other things equal, co-operative members who were exposed to extension activities were more likely to adopt a modern variety rice or use fertiliser than non co-operative members who sere not exposed to any of the extension activities. v Comprehensive government programmes to ensure the availability of fertilisers, effective administration of credit, strengthening of extension services and providing other infrastructure would be vital for adoption of a modern variety rice and use of fertiliser. This in turn could lead to increase in farm productivity.